PENTINGNYA MEMBANGUN KEPERCAYAAN DIRI SISWA SD MELALUI APRESIASI NON-AKADEMIK - Nurfadilah Anasya; Elfia Sukma; Inggria Kharisma (LPPM IAD Probolinggo, 2026)
This study aims to examine the importance of non-academic appreciation in building the confidence of elementary school students. The research uses a qualitative approach with a type of library research that focuses on the analysis of various scientific literature on strengthening self-efficacy, non-academic awards, and psychological development of elementary school-age children. Data collection was carried out through documentation studies of books, journal articles, and research results obtained from Google Scholar, ScienceDirect, and the Garuda Portal. Data analysis was carried out using content analysis techniques through the stages of data reduction, data classification, data interpretation, and conclusion drawn. The results of the study show that non-academic appreciation has a significant influence on the formation of confidence and self-efficacy of elementary school students. Recognition of talents in the fields of art, sports, leadership, and social character can increase intrinsic motivation, courage to try new things, and students' mental resilience in the face of academic pressure. In addition, non-academic appreciation also acts as a psychological buffer that helps students reduce their sense of inferiority due to academic comparisons in the school environment. This study concludes that elementary schools need to build a learning environment that is inclusive and friendly to the diversity of students' potential through collaboration between teachers and parents in providing recognition for each child's talents and efforts.